A BIM-BASED STUDY ON THE EFFECT OF WINDOW-TO-WALL RATIO (WWR) ON ELECTRICAL ENERGY EFFICIENCY - Narwastuti, Gabrilia Dewi; Cahya Adisa, Aurora; Azizah, Yuni (Department of Architecture and Planning, Faculty of Engineering, Universitas Gadjah Mada, 2025)
The construction sector's reliance on non-renewable energy sources affects the sustainability of the world's energy supply. Household electrical energy consumption is one of the main factors contributing to Indonesia's electricity consumption; hence, the residential typology is researched for energy efficiency. This study aims to analyze the variations of window-to-wall ratio (WWR) effect on electrical energy consumption in developing type 55 houses in Sleman, DIY. Several WWR percentage scenarios were created to determine the most effective value for improving building energy efficiency. This research was conducted with the quantitative method using the Building Information Modeling (BIM) simulation through Autodesk Revit software and the Green Building Studio (GBS) plugin. According to the research, WWR impacts buildings' electrical energy usage, particularly for HVAC systems, with a range of around 41% to 52% usage. Alternative scenarios with lower WWR can reduce annual electrical energy consumption and specific energy use intensity (EUI) values. In addition, a 5.8% savings in electricity costs can be obtained with the lowest WWR scenario. Thus, it can be concluded that variations of WWR affect electrical energy consumption and costs in residential buildings.